Influence of LCL Output Filter Parameter Changing on D-STATCOM Compensation Characteristics - ZHANG Xingru (机车电传动)
Aim at the problem of D-STATCOM output containing plenty of switching ripple, LCL filter was designed. Influence of LCL filter parameters on the compensation characteristic of D-STATCOM was studied. Considering the compensation capacity of the D-STATCOM, the compensation current switch ripple, the grid THD, the resistance loss and the other factors, a method of designing LCL filter was presented, and the compensation characteristic of the D-STATCOM with the LCL filter was researched with simulation. The results proved that the output filter designed in this method had very good inhibitory effect on high-frequency switch ripple, and greatly improved the compensation performance of the D-STATCOM.